Civilized Drinking: Alcohol and Society in New Brunswick, 1945-1975 - Marquis, Greg (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2000)
AbstractAlcohol policy in New Brunswick was contested terrain. Following the political defeat of prohibition, the province introduced government liquor stores in 1927, but refused for more than three decades to license public establishments, although Legions and private clubs enjoyed a quasi-legal status. By the end of the Second World War, the province had one of the lowest liquor consumption rates in Canada, a small but vocal temperance movement, and a fairly dry hospitality sector. During the 1960s and 1970s, access to alcohol was liberalized with the licensing of taverns and dining rooms, the decriminalization of public drunkenness, and the lowering of the drinking age to 19. Meanwhile, the public health, social service, legal and voluntary sectors lobbied for prevention and treatment programs based on the disease concept of alcoholism, rather than the moralistic arguments of the older temperance movement. By 1975, it was clear that New Brunswick's alcohol control policies mirrored the wider Canadian experience as residents were treated to competing discourses: drinking was a modern, reasonable, and fashionable recreation but alcohol was society's most widespread and costly addictions problem.